Pengembangan E-LKPD Berbasis Pembelajaran Penemuan untuk Meningkatkan Keterampilan Pengambilan Keputusan dan Sikap Ilmiah Peserta Didik Kelas XI IPA - I Gede Karunia Soenarko; Agus Abhi Purwoko; Saprizal Hadisaputra (Postgraduate, University of Mataram, 2022)
The goal of this study is to create an E-worksheet product based on discovery learning that will help students improve their decision-making skills and scientific attitudes. This E-worksheet was created using the 4D development methodology, which includes the processes of define, design, develop, and disseminate. Students in class XI science SMAN 6 Mataram served as test subjects for this study. The limited trial is taught in one lesson, while the wide trial is taught in two classes. The ANCOVA test, descriptive percentage techniques, and percentage of agreement were used to analyze the data. The practicality data analysis revealed that teachers and students responded with a percentage of 80 and 86.42 percent, respectively, showing that the E-worksheet evolved in the practical category. The results of the effectiveness test using the ANCOVA test obtained Fcount > Ftable (8.28 > 3.98) on decision-making skills and Fcount > Ftable (6.94 > 3.98) on scientific attitude with a significant level of 5%. The null hypothesis (H0) is rejected, which means that E-worksheet influences discovery learning to improve students' decision-making skills and scientific attitudes in grade-eleventh science students. The E-worksheet based on discovery learning is practical and successful for enhancing students' decision-making skills and scientific attitudes toward grade-eleventh science students, according to the research objectives and findings.